Texts from Swedish Public Employment Service - Dahlberg, Simon; Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Parallel texts downloaded from the websites of the Swedish Public Employment Agency.

Parallel texts downloaded from the website of Swedish Public Employment Service.
What was actually downloaded were pdf files. The txt files that are available are the result of running the pdf files through the pdftotext command from an ubuntu shell.

Parallella texter nedladdade från Arbetsförmedlingens webbplats.
Det som nedladdades var pdf-filer. De txt-filer som finns tillgängliga är resultat ur en körning av kommandot pdftotext i ubuntu-skal.
Texter från Arbetsförmedlingen
Keywords: labour policy; arbetsmarknadspolitik; Migration; Migration; Employment; Sysselsättning; Unemployment; Arbetslöshet; Social welfare policy; Välfärdspolitik; Social welfare systems/structures; Sociala välfärdssystem/-strukturer; Specific social services: use and availability; Specifika sociala tjänster: användning och tillgänglighet; Other Social Sciences not elsewhere specified; Övrig annan samhällsvetenskap; Comparative Language Studies and Linguistics; Jämförande språkvetenskap och allmän lingvistik; Labour and employment policy; Arbetsmarknads- och sysselsättningspolitik; Public Administration Studies; Studier av offentlig förvaltning